Change in instantaneous wave-free ratio in the donor artery in multivessel coronary disease: a case report - F. B. Shukurov; T. P. Baronets; B. A. Rudenko; D. K. Vasiliev; D. A. Feshchenko (Российский кардиологический журнал, 2022)
Patients with multivessel coronary artery disease require an individual approach when choosing tactics for myocardial revascularization. In some cases, additional methods for assessing the stenosis significance should be used, such as measuring the fractional or instantaneous wave-free ratio, in order to decide on the most optimal and safe management of a patient. The article presents a case report of a change in the functional significance of stenosis of the left anterior descending artery (donor artery) after endovascular treatment in the right coronary and circumflex artery systems in a patient with three-vessel coronary disease and diabetes.